Cultivating Critical Citizenship and Democratic Resilience Among Indonesian Youth: A Participatory Framework for Preventing Violent Extremism - Zulfachry, Zulfachry; Rachmat, Zul (PUBLICUS : JURNAL ADMINISTRASI PUBLIK, 2025)
This study examines strategies for building national integrity among Indonesian youth as a countermeasure against radicalism. Radicalism, defined as ideological movements seeking drastic social and political change through extreme means, poses significant threats to Indonesia's national unity. Youth, as the nation's assets and future leaders, are particularly vulnerable to radical recruitment due to their idealism and energy. National integrity encompasses qualities of wholeness, honesty, and consistency toward truth that manifest in dignified behavior. The research identifies that radical movements in Indonesia, including terrorism and separatist activities, frequently involve youth participation, making it crucial to strengthen their nationalist and patriotic values. The study proposes nine strategic approaches: (1) instilling nationalism through the four pillars of nationhood (Pancasila, 1945 Constitution, NKRI, Bhinneka Tunggal Ika); (2) developing patriotism through family, educational, and institutional environments; (3) cultivating the spirit and values of 1945 struggle; (4) implementing character education through formal, informal, and non-formal channels; (5) enhancing positive youth roles through empowerment programs; (6) educating about Indonesia's unity history; (7) forming attitudes embracing diversity; (8) exploring and implementing nationalist values; and (9) fostering brotherhood through youth organizations. This comprehensive approach aims to equip Indonesian youth with strong national identity and critical thinking to resist radical ideologies while maintaining their role as agents of positive change.